Optimum seeding density and seedling age for the outstanding yield performance of Japonica rice using crop straw boards for seedling cultivation - Ling, Yufei; Hu, Qun; Fu, Dihui; Zhang, Kaiwei; Xing, Zhipeng; Gao, Hui; Wei, Haiyan; Zhang, Hongcheng (Frontiers in Plant Science, 2024)
Crop straw boards, a novel nursery material, has proven effective for cultivating dense, young rice seedlings suitable for mechanized transplanting, thereby saving labor. However, under high-density nursery conditions, the biomass accumulation and yield formation in rice vary with different seedling ages, necessitating exploration of optimal seeding densities and seedling ages to achieve high yields. This study aims to determine the appropriate seeding densities and seedling ages using crop straw boards to maximize rice yield. Over two years, field studies were conducted using crop straw boards for rice cultivation at seeding densities of 150, 200, 250, 300, and 350 g/tray (labeled as D1, D2, D3, D4, and D5) and seedling ages of 10, 15, 20, and 25 days (labeled as A1, A2, A3, and A4).The results indicated that D4A2 significantly enhanced tiller number, dry matter accumulation, and photosynthetic capacity, resulting in a yield increase of 2.89% compared to the conventional method of D1A3. High-density and short-aged seedlings cultivated with crop straw boards can enhance rice yield by improving photosynthetic capacity and crop quality. This study emphasizes the importance of using crop straw boards for rice nursery practices, as well as selecting the appropriate seeding densities and seedling ages for optimizing rice production.